The Influence of the Merdeka Mengajar Platform on the Development of Teachers’ Competency in Junior High Schools - Agustina, Duwi; Lestari, Neta Dian (PPSDP International Journal of Education, 2025)
This study aims to analyze the influence of the Merdeka Mengajar Platform on the development of teacher competencies in junior high schools in Mesuji District. In the digital era, this platform is presented by the government to support improving the quality of learning and teacher professional development through access to teaching materials, learning evaluations, and independent training. This study uses a literature review approach by reviewing a number of national scientific articles related to the implementation and impact of the Merdeka Mengajar Platform on teacher pedagogical, professional, and digital competencies. This study found that the use of the Merdeka Mengajar platform significantly contributed to improving teacher pedagogical and professional competencies through the provision of curriculum-appropriate materials and technology skills training. The results of the study showed that teachers experienced increased skills in preparing learning plans based on the Merdeka curriculum, as well as increased competence in utilizing technology for a more effective and efficient learning process. The novelty of this study lies in the focus of the analysis of the impact of the platform on a specific area, namely Mesuji District, which previously received less attention in national research. The contribution of this study is to provide recommendations for policymakers and platform developers to continue to improve relevant features and content and for schools to encourage the use of this platform as an integral part of teacher professional development in the future.